2023
DOI: 10.1073/pnas.2302048120
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the underestimated direct emissions of nitrous acid (HONO)

Qian Zhang,
Pengfei Liu,
Yan Wang
et al.

Abstract: Gaseous nitrous acid (HONO) is a critical source of hydroxyl radicals (OH) in the troposphere. While both direct and secondary sources contribute to atmospheric HONO, direct emissions have traditionally been considered minor contributors. In this study, we developed δ 15 N and δ 18 O isotopic fingerprints to identify six direct HONO emission sources and conducted a 1-y case study on the isotopic composition of atmospheric HONO at rural and urban sites. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…Ground sources of HONO have been recognized as potentially important contributors. , The HONO isotope observations in China show significant influences of fertilizer applications and livestock farms . Ground conversion from NO 2 is found to be a minor HONO source in that study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground sources of HONO have been recognized as potentially important contributors. , The HONO isotope observations in China show significant influences of fertilizer applications and livestock farms . Ground conversion from NO 2 is found to be a minor HONO source in that study.…”
Section: Methodsmentioning
confidence: 99%
“…HONO is produced through the gas-phase reaction of nitric oxide (NO) and OH (R1) . Direct emissions from combustion activities, such as vehicle exhaust and biomass burning (BB) can also contribute to HONO levels. In recent years, observations in a variety of locations have found other daytime HONO sources to be important. , Soil emissions of HONO have been found to be potentially important for regions with livestock farming or after fertilization, highlighting the need of detailed quantification in future studies . Moreover, various HONO production pathways have been proposed based on field measurements and laboratory experiments, with heterogeneous reactions highlighted as crucial contributors. For example, studies have demonstrated the importance of heterogeneous nitrogen dioxide (NO 2 ) conversion on ground surfaces (eq S3) as an important nocturnal HONO source .…”
Section: Introductionmentioning
confidence: 99%
“…So far, HONO sources include direct emissions (e.g., emission from soil), gas-phase homogeneous reactions, heterogeneous NO 2 conversion, , and photolysis of nitric acid, nitrate, and nitroaromatic. , Recent studies have underscored the existence of strong unknown HONO sources in forests and agricultural regions, ,, as well as in urban areas, particularly its daytime sources. Of particular interest is the potential role of motor vehicle exhaust in ambient HONO levels, considering that motor vehicles have been reported to emit HONO directly as well as a cocktail of volatile organic compounds (VOCs), NO x , and other reactive substances. The interaction between these components under various atmospheric conditions could give rise to novel pathways for the HONO formation.…”
Section: Introductionmentioning
confidence: 99%
“…The release from soil nitrite is one important primary source of HONO (Su et al, 2011;Wu et al, 2019), the biological soil crusts can accelerate the HONO emission in drylands (Weber et al, 2015), fertilization behavior of agricultural fields remarkably enhance the emission of HONO (Xue et al, 2021), and denitrification is one major HONO production pathway in boreal agricultural fields (Bhattarai et al, 2021). Meanwhile, livestock farming is also identified as one important primary emission source of HONO (Zhang et al, 2023a). (b) Homogeneous reaction of OH +NO, which usually occurs in polluted areas, the contribution of this recombination pathway to HONO may be significant during daytime with high NO and OH concentration (Gu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%